2014
DOI: 10.1038/bjc.2014.511
|View full text |Cite
|
Sign up to set email alerts
|

Mutational profiling of familial male breast cancers reveals similarities with luminal A female breast cancer with rare TP53 mutations

Abstract: Background:Male breast cancer (MBC) is still poorly understood with a large proportion arising in families with a history of breast cancer. Genomic studies have focused on germline determinants of MBC risk, with minimal knowledge of somatic changes in these cancers.Methods:Using a TruSeq amplicon cancer panel, this study evaluated 48 familial MBCs (3 BRCA1 germline mutant, 17 BRCA2 germline mutant and 28 BRCAX) for hotspot somatic mutations and copy number changes in 48 common cancer genes.Results:Twelve misse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
2
17
1
Order By: Relevance
“…We reported the occurrence of PIK3CA amplification at higher frequency than that previously reported in MBC [26]. The frequency of PIK3CA amplification found in our study is consistent with that reported in FBC [2729].…”
Section: Discussionsupporting
confidence: 92%
“…We reported the occurrence of PIK3CA amplification at higher frequency than that previously reported in MBC [26]. The frequency of PIK3CA amplification found in our study is consistent with that reported in FBC [2729].…”
Section: Discussionsupporting
confidence: 92%
“…Somatic HRAS‐ activating PVs are frequently found in salivary gland, urinary tract, upper aerodigestive tract and cervical cancer, but are rarely observed in breast cancer (< 1%) . Moreover, duplications of HRAS have only been found in tumors of male breast cancer patients carrying a pathogenic germline BRCA2 variant . It is unknown whether or not the observed HRAS duplication has a dosage effect or if aberrant HRAS expression influences tumor development at all.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Moreover, duplications of HRAS have only been found in tumors of male breast cancer patients carrying a pathogenic germline BRCA2 variant. 37 It is unknown whether or not the observed HRAS duplication has a dosage effect or if aberrant HRAS expression influences tumor development at all. To the best of our knowledge, this is the first report of a germline HRAS duplication identified in HBOC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In The Cancer Genome Atlas (TCGA) project, six MaBCs were included, of which all were of luminal subtype, two harbored PIK3CA somatic mutations and none had TP53 mutations (13). The repertoire of genetic alterations affecting 48 common cancer genes has been analyzed in familial MaBCs (BRCA1, BRCA2 and BRCAX patients) (14); these tumors were found to display a mutational landscape similar to that of luminal A FBCs, with PIK3CA being the most commonly mutated gene (17%) in addition to infrequent TP53 and PTEN mutations (4% and 2%, respectively) (14). Substantial differences were detected, however, between BRCA2 and ‘BRCAX’ patients.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial differences were detected, however, between BRCA2 and ‘BRCAX’ patients. Whilst TP53 mutations were only found in BRCA2 cases (14), PIK3CA mutations were significantly more prevalent in BRCAX patients (15), suggesting that BRCA2-associated MaBCs may have distinct genomic features, possibly due to the DNA repair defect caused by BRCA2 mutations.…”
Section: Introductionmentioning
confidence: 99%